Detection of coding microsatellite frameshift mutations in DNA mismatch repair‐deficient mouse intestinal tumors. Issue 11 (11th September 2014) - Woerner, Stefan M.; Tosti, Elena; Yuan, Yan P.; Kloor, Matthias; Bork, Peer; Edelmann, Winfried; Gebert, Johannes
<x xml:space="preserve">Abstract</x> Different DNA mismatch repair (MMR)‐deficient mouse strains have been developed as models for the inherited cancer predisposing Lynch syndrome. It is completely unresolved, whether coding mononucleotide repeat (cMNR) gene mutations in these mice can contribute to intestinal tumorigenesis and whether MMR‐deficient mice are a suitable molecular model of human microsatellite instability (MSI)‐associated intestinal tumorigenesis. A proof‐of‐principle study was performed to identify mouse cMNR‐harboring genes affected by insertion/deletion mutations in MSI murine intestinal tumors. Bioinformatic algorithms were developed to establish a database of mouse cMNR‐harboring genes. A panel of five mouse noncoding mononucleotide markers was used for MSI classification of intestinal matched normal/tumor tissues from MMR‐deficient (Mlh1−/−, Msh2−/−, Msh2LoxP/LoxP) mice. cMNR frameshift mutations of candidate genes were determined by DNA fragment analysis. Murine MSI intestinal tumors but not normal tissues from MMR‐deficient mice showed cMNR frameshift mutations in six candidate genes (Elavl3, Tmem107, Glis2, Sdccag1, Senp6, Rfc3). cMNRs of mouse Rfc3 and Elavl3 are conserved in type and length in their human orthologs that are known to be mutated in human MSI colorectal, endometrial and gastric cancer. We provide evidence for the utility of a mononucleotide marker panel for detection of MSI in murine tumors, the existence of cMNR instability in MSI murine tumors, the utility of mouse subspecies DNA for identification of polymorphic repeats, and repeat conservation among some orthologous human/mouse genes, two of them showing instability in human and mouse MSI intestinal tumors. MMR‐deficient mice hence are a useful molecular model system for analyzing MSI intestinal carcinogenesis. © 2014 Wiley Periodicals, Inc.